Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome